Rapid, Nitric Oxide Synthesis-Dependent Activation of MMP-9 at Pericyte Somata During Capillary Ischemia in vivo - Underly, Robert G.; Shih, Andy Y. (Frontiers in Physiology, 2021)
Nitric oxide serves essential roles in normal vascular physiology, but paradoxically contributes to vascular pathology in disease. During brain ischemia, aberrant nitric oxide levels can cause cellular injury through induction of nitrosative/oxidative stress and post-translational activation of matrix-metalloproteinase-9 (MMP-9). We recently demonstrated that brain pericyte somata were associated with very early and localized MMP-9 activation along capillaries during cerebral ischemia, leading to focal blood-brain barrier disruption. Here, we tested whether this effect was dependent upon nitric oxide production. In vivo two-photon imaging was used to directly visualize MMP9 activity using a FITC-gelatin probe and leakage of intravenous dye during photothrombotically-induced capillary ischemia. Results showed that the NOS inhibitor, L-NIL, at concentrations affecting both iNOS and constitutive NOS isoforms, attenuated capillary leakage at pericyte soma-specific locations and substantially reduced FITC-gelatin cleavage. We also found that combined administration of L-NIL and anisomycin, an inhibitor of protein synthesis, led to near complete elimination of FITC-gelatin cleavage and vascular leakage. These results indicate that both nitric oxide synthase and new protein synthesis are involved in the rapid activation of MMP-9 at somata of capillary pericytes during ischemia.